Through the Lens of Tension: An Art Educator’s Quest to Understand if the Art her Students Produce has Honour and Purpose as a Product of Integrity and Veracity - Bloomfield, Louise (Curtin University, 2018)
I invite the reader into my world as an art educator and as an artist to reveal my art practice and to share insights into my philosophy around the enigma of visual art through the lens of tension. Art education is not only about producing imagery but is a means to explore the world and to come to know the self—to act with both private and public intelligence and in a phenomenological manner.